THE EFFECT OF COUNSELING AND ECONOMIC STATUS ON PATIENT KNOWLEDGE ABOUT DRUGS - Elyna Yanti; Jenny Marlindawani Purba; Laura M Siregar; Myrnawati CH; Mido Ester Sitorus (Program Studi Ners UNIVERSITAS SARI MUTIARA INDONESIA, 2023)
Counselling and economic status affect patients’ knowledge of drugs. The purpose of this study was to identify the effect of counselling using audio-visual media and economic status on patients’ knowledge of drugs at the Pharmacy Installation of Langsa Hospital. This research was a true experiment with a 2x2 by level design. The population included the outpatients at the Pharmacy Installation at Langsa Hospital. A total of 28 outpatients served as research samples; consisting of the experimental group (n=14) and the control group (n=14). Consecutive sampling was employed as sampling technique. The results showed that there was a significant difference in the average knowledge between the patients who received counselling using audio-visual media and those using leaflets (p-value = 0.005). There was a significant difference in the mean scores of knowledges about drugs based on the economic status in the experimental group (p-value = 0.008) and in the control group (p-value = 0.005). There was no interaction between counselling using media and economic status on patients’ knowledge about drugs (p-value = 0.504). There was a significant difference in the mean scores of knowledges between patients received counselling using audio-visual media and those using leaflet and with high economic status (p-value = 0.004) and in patients with low economic status (p-value = 0,011). This study concludes that giving counselling to patients using audio visual media increased patient knowledge on both patients with high economic and low economic status. It is suggested that the management of Langsa Hospital regularly organizes health promotion through counselling using audio-visual media in the waiting room or the pharmacy installation to increase patients’ knowledge of drugs.